Comparison of the Effectiveness of Dialectical Behavior Therapy and Emotion-Focused Therapy on Communication Patterns and Marital Intimacy in Marital Infidelity Among Women - Badanfiroz, Ali; Abolghasemi, Abbas; Khosrojavid, Mahnaz; Soltani Shal, Reza (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to compare the effectiveness of Dialectical Behavior Therapy (DBT) and Emotion-Focused Therapy (EFT) on communication patterns and marital intimacy in cases of marital infidelity among women in the city of Isfahan. Methods and Materials: The research method was quasi-experimental, utilizing a pretest-posttest design with control and experimental groups. The statistical population of this study included all women with experiences of marital infidelity who sought counseling in the city of Isfahan in 2023. The sample consisted of 45 women with experiences of marital infidelity who sought counseling services in Isfahan, selected through convenience sampling and randomly assigned to two experimental groups—DBT and EFT—and one control group. Data were collected using the Marital Infidelity Questionnaire by Yenisey and Kokdemir (2006), the Communication Patterns Questionnaire by Christensen and Salovey (1984), the Marital Intimacy Questionnaire by Bagarozy (2001), and the Emotion Regulation Questionnaire by Gross and John (2003). Data analysis was conducted using univariate and multivariate analysis of covariance. Findings: The results indicated that both Emotion-Focused Therapy and Dialectical Behavior Therapy were effective in improving communication patterns and marital intimacy among women. Furthermore, the findings revealed that Emotion-Focused Couples Therapy had a greater impact than Dialectical Behavior Therapy on improving these variables. Conclusion: Based on the findings, both EFT and DBT can be utilized as effective, cost-efficient, and practical approaches with wide applicability in improving and repairing couple relationships.